Python for secret agents : analyze, encrypt, and uncover intelligence data using python, the essential tool for all aspiring secret agents /: analyze, encrypt, and uncover intelligence data using python, the essential tool for all aspiring secret agents. (2014) - Lott, Steven F
No abstract available